On fibrinolysis and malignancy - Layer, G; Layer, Graham T. (1990)
Abnormalities of fibrinolysis have been recognised in malignancy. Studies have suggested that following the resection of colorectal tumours, increased fibrinolysis is associated with increased circulating malignant cells and a paradoxically prolonged survival. A "fibrin barrier" has been demonstrated histologically around some tumours including breast carcinomas. Certain tumours are able to degrade fibrin and this tissue fibrinolytic activity might influence cell shedding and metastatic implantation. Fibrinolysis is plasmin-mediated and initiated by plasminogen-activating enzymes: tissue plasminogen activator (tPA) and urokinase-type plasminogen activator (UK). Tissue (extravascular) fibrinolysis has previously been demonstrated but its estimation has been hampered by difficulties in extraction of plasminogen activators from tissues. A cryodestruction method was developed to overcome these problems by fragmenting tissues obtained surgically, releasing plasminogen activators into solution. The extracts or their supernatants could be used to estimate the fibrinolytic activity (capacity) of the tissues on plasminogen-rich fibrin plates, and their component plasminogen activators by immunoassays and gel electrophoresis. This thesis compares the tissue fibrinolytic activity of 56 carcinomas of the breast with that of 19 biopsies of benign disease and normal breast. The centre and edge of each tumour, and the surrounding "normal" breast was analysed. The relationships between the fibrinolytic activity of the malignant breast tissue with systemic fibrinolysis, tumour size, axillary node status and patients' survival were studied. The tissue extract supernatants were analysed for tPA or UK by new immunoassays using specific polyclonal antibodies. An ELISA measured plasminogen activator antigen and a bioimmunoassay estimated the functional plasmin-dependent activity. The enzymes in the tissue extracts were separated according to molecular weight by SDS-polyacrylamide gel electrophoresis. The gels were incubated with a plasminogen-rich fibrin-overlay incorporating specific polyclonal antisera in different combinations to identify and discriminate tPA from UK (zymography). Tissue fibrinolysis was significantly elevated in malignant (0.32±;0.04, mean u/ml±sem) compared with benign breast extracts (0.14±0.02; t=3.40, P<0.001) on fibrin plates. Breast carcinoma fibrinolytic activity showed no relation to tumour size or systemic fibrinolysis. Extracts of multiple areas from 26 breast carcinomas and 13 benign biopsies were analysed for tPA and UK using the immunoassays. Levels of both tPA antigen and activity were similar, as were those for UK, suggesting the absence of inhibitors (r=0.79, df=87, P<0.001). Both malignant and benign tissues contained similar levels of tPA antigen and activity. However, the malignant showed significantly greater levels of UK antigen and activity than benign tissues. The zymograms confirmed that UK was almost exclusively and significantly confined to the malignant tissues, supporting the results of the immunoassays. Animal experiments were performed to discover if the manipulation of systemic fibrinolysis affected the behaviour of a tumour model; to assess whether the increase in plasminogen activators in malignant tissue was an unrelated secondary phenomenon. The spontaneously-metastasising Lewis lung carcinoma was implanted subcutaneously in groups of C57Black mice after significant alterations in fibrinolysis were achieved by the intraperitoneal administration of urokinase, intramuscular stanozolol and oral aminocaproic acid. Significantly larger primary tumours were found in animals with depressed systemic fibrinolysis due to urokinase and stanozolol, than in controls. Urokinase also promoted the development of pulmonary metastases. These studies have demonstrated a significantly increased tissue fibrinolytic activity in extracts of malignant breast compared with benign tissues. A significant and differential increase in urokinase-type plasminogen activator in the malignant compared with the benign extracts has been discovered. The promotion of growth of the Lewis lung carcinoma by urokinase and stanozolol, associated with the depression of systemic fibrinolysis, supports the hypothesis that the components of fibrinolysis have a role in malignancy.